2021
DOI: 10.1038/s41409-021-01528-y
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus initial steady state level in post-transplant cyclophosphamide-based GvHD prophylaxis regimens

Abstract: Post-transplant cyclophosphamide (PTCy) combined with tacrolimus (TAC) as graft-versus-host disease (GvHD) prophylaxis post-hematopoietic cell transplantation (HCT) is safe and effective. Optimal serum levels of TAC in this combination remain undetermined. We hypothesized that TAC at initial steady state (TISS) of <10 ng/mL could promote optimal transplant outcomes and prevent TAC-associated toxicities. We retrospectively analyzed a consecutive case series of 210 patients who received PTCy/TAC-based prophylaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Little is known about the relationship between Tac C 0 and the incidence of aGVHD in patients receiving PTCy. Survival outcomes have been reported similarly in patients with TISS < 10 ng/mL and ≥10 ng/mL early after alloHSCT receiving PTCy-based GVHD prophylaxis [26]. Moreover, TISS < 10 ng/mL was associated with a lower risk of viral infection, with no differences in the bloodstream or fungal infections.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Little is known about the relationship between Tac C 0 and the incidence of aGVHD in patients receiving PTCy. Survival outcomes have been reported similarly in patients with TISS < 10 ng/mL and ≥10 ng/mL early after alloHSCT receiving PTCy-based GVHD prophylaxis [26]. Moreover, TISS < 10 ng/mL was associated with a lower risk of viral infection, with no differences in the bloodstream or fungal infections.…”
Section: Discussionmentioning
confidence: 67%
“…Studies have evaluated the optimal range of blood concentrations of Tac early after alloHSCT for preventing GVHD. Although several of these studies reported that the incidence of aGVHD was unaffected by Tac concentrations, more recent studies have shown an association between low Tac levels and a higher risk of aGVHD [15][16][17]25,26]. For example, an analysis of a group of patients who underwent HLA-matched unrelated donor transplantation, most of whom were administered a MAC regimen and all of whom received intravenous Tac and short-term MTX, with a target Tac level set at 10 to 20 ng/mL, found that low mean Tac blood concentrations during the second and third weeks after transplantation were significant risk factors for aGVHD [16].…”
Section: Discussionmentioning
confidence: 99%
“…These data could have relevant clinical implications after alloHSCT. Lower Tac C 0 within the early period after alloHSCT has been associated with a higher incidence of acute GVHD [9,10] despite therapeutic drug monitoring and dose adjustment. Accordingly, we have observed a higher rate of clinically significant acute GVHD and AKI in intermediate and extensive Tac metabolizers patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exposure to Tac during the immediate period after the HSCT period is of utmost importance to prevent subsequent GVHD [4,7,8]. Furthermore, subtherapeutic Tac trough concentrations (C 0 < 5 ng/mL) at 48 h or 7 days after transplant has been associated with an increased incidence of acute GVHD (GVHD) [9,10].…”
Section: Introductionmentioning
confidence: 99%